2011
DOI: 10.1007/s13187-011-0193-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cancer Survivorship Care: Oncology Nurses’ Educational Needs and Preferred Methods of Learning

Abstract: Oncology nurses are essential in all phases of cancer care; however, their role in survivorship care is unclear. To better understand the self-reported knowledge and educational needs on topics of survivorship care and oncology nurses’ learning preferences, an online survey was conducted. Respondents self-reported knowledge level for 31 care topics, identified areas of most interest, topics needed to assist patients and address patient questions, and reported participation in continuing education and preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 13 publications
2
25
0
2
Order By: Relevance
“…To address these workforce issues, psychosocial providers need to be integrated into oncology settings, and more education about the needs of cancer survivors will be needed for mental health providers, oncologists, PCPs, and nurses. Innovative educational programmes for physicians, nurses, and psychosocial providers have been developed as part of training curricula 6062 and continuing professional education 63,64 to address this requirement, but their quality and accessibility need to be ensured to educate the workforce at large.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…To address these workforce issues, psychosocial providers need to be integrated into oncology settings, and more education about the needs of cancer survivors will be needed for mental health providers, oncologists, PCPs, and nurses. Innovative educational programmes for physicians, nurses, and psychosocial providers have been developed as part of training curricula 6062 and continuing professional education 63,64 to address this requirement, but their quality and accessibility need to be ensured to educate the workforce at large.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…In a survey of 51 students who completed an elective palliative care subject Bush and Shahwan-Akl [10] students felt that palliative care should be compulsory in all undergraduate nursing courses, however, Klemp et al, [34] indicates that undergraduate courses were inadequate in this area and that postgraduate education was required to address this gap. Some authors [13,14] warn against limiting education on end of life care to a single subject, but rather suggest that it is more effective to integrate this aspect of nursing education across the undergraduate course.…”
Section: The Death Experience For Different Patient Populationsmentioning
confidence: 99%
“…[30] Online learning will continue to grow in popularity as it presents a feasible and accessible option for more nurses in practice. [27] Overall, the majority of participants viewed the virtual ACs positively, while a few participants did not particularly like them. This may reflect that many nurses were more comfortable or open to newer technologies.…”
Section: Discussionmentioning
confidence: 93%
“…Oncology nurses have reported that online access to continuing education is a good vehicle for leaning. [27] The necessity to partake in continuing education is important as is online access for nurses as it not only meets professional…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation